2009
DOI: 10.1111/j.1365-2427.2009.02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Does sulphate enrichment promote the expansion of Typha domingensis (cattail) in the Florida Everglades?1

Abstract: 1. The expansion of Typha domingensis into areas once dominated by Cladium jamaicense in the Florida Everglades has been attributed to altered hydrology and phosphorus enrichment, although increased concentrations of sulphate and phosphorus often coincide. The potential importance of hydrogen sulphide produced from sulphate in the expansion of Typha has received little attention. The present study aimed to quantify the comparative growth and photosynthetic responses of Cladium and Typha to sulphate ⁄ sulphide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…These locations are also heavily enriched with phosphorus from agricultural runoff, and eutrophication has been suggested as the principal cause of this change in macrophyte dominance (Childers et al, 2003;Miao et al, 2000). Sulfide toxicity may also play a role, however, because the observed sulfide levels can exceed those toxic to Cladium (Li et al, 2009). The effects of sulfide on other Everglades flora are not known.…”
Section: Sulfide Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…These locations are also heavily enriched with phosphorus from agricultural runoff, and eutrophication has been suggested as the principal cause of this change in macrophyte dominance (Childers et al, 2003;Miao et al, 2000). Sulfide toxicity may also play a role, however, because the observed sulfide levels can exceed those toxic to Cladium (Li et al, 2009). The effects of sulfide on other Everglades flora are not known.…”
Section: Sulfide Toxicitymentioning
confidence: 99%
“…Li et al (2009) demonstrated that sulfide impacts Cladium at 7,480 µg l −1 in soil pore water. This level of sulfide occurs in areas where surface water sulfate concentrations routinely exceed 40 mg l −1 (<5% of the Everglades; Scheidt and Kalla, 2007).…”
Section: Need For Sulfur Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an emergent macrophyte commonly called cattail which leaves are amphistomatic with sclerenchymatous fibers forming groups between the palisade and spongy parenchyma (Henry, 2003). Cattail species may cause many problems colonizing non-native environments, for example, Li et al (2009) described the problem involving T. domingensis colonization reducing Cladium jamaicense populations in the Everglades. However, despite of some spots show high colonization of T. domingensis, occupying more than 50% of the area, in some spots plants do not colonize even 50% of its area.…”
Section: Introductionmentioning
confidence: 99%
“…This population behavior may damage hydroelectric energy production, river traffic, agricultural irrigation and nautical sports practice (Thomaz, 2002). Cattail population growth, in special, may decrease the size of other macrophyte population, as reported to Cladium jamaicense by Li et al (2009) and Eleocharis spp. by Macek et al (2010).…”
Section: Introductionmentioning
confidence: 99%